Investigation of Science Technology Ecocultural Society (STEcS) Model to Enhance Eco Critical Thinking Skills - Wahyuni Purnami; Sarwanto Sarwanto; Suranto Suranto; Retno Dwi Suyanti; Mauro Mocerino (Yayasan Keluarga Guru Mandiri, 2021)
The Purpose of this study was to investigate the goodness fit model of Eco Critical Thinking Skills (ECTS) and effectiveness Science Technology Ecocultural Society (STEcS) model in elementary school teacher education programs. Participants in this study were 229 students, taken from 3 universities. The data collection method was an open ended essay test and questioner. The research analysis the goodness fit model used was Lisrel 8 and effect size analysis. The results of the investigation indicated that the construct analysis on the instrument model was categorized as a good fit model category with P-value 0.28 ( 0.05), RMSEA 0.02 (0.08) and other indicators of fit model were above 0.90. Analysis of the effect size based on Cohen's d criteria of 1.391 ( 0.08) is classified as very high criteria. This research concluded that instrument is good fit, Interpretation dimension is highest support. STEcS model is effective to enhance Eco Critical Thinking Skills at elementary school teacher education program. The research implication is Eco Critical Thinking Skills of students can be improved through the application of the STEcS model. The STEcS model is an alternative model for preparing 21st century learning.